Debt Issues and Earnings Management - Sincerre,Bianca Piloto (2016)
ABSTRACT The aim of this paper is to analyze earnings management (EM) surrounding debenture issues of companies listed on the BM&FBOVESPA. EM is an intentional intervention in external financial reports in order to obtain some private gain. This practice is especially important at the time of issuing debentures because if earnings are inflated, investors may pay an artificially high price. To measure earnings management, current discretionary accruals were used as a proxy, based on the Modified Jones and Modified Jones with ROA econometric models. All of the regressions considered the fixed effects of the companies and the time series effects of the analyses. Evidence was found that companies inflate their financial results in the issuing period in order to positively influence their investors. The results suggest that there is EM in the quarter preceding the issue (t = - 1), indicating the influence that investors may have been under when making the decision to invest in debentures from these companies. In addition, it was verified that companies with higher debt, profitability, and sales growth ratios have higher levels of earnings management. The reputation of the auditor was not statistically significant regarding reductions in the level of management. The results also show that companies listed on Level II and New Market had higher levels of management when considering the Modified Jones with ROA model. Therefore, it can be concluded that there is a greater level of earnings management in companies that issue debentures in the period preceding the event. Finally, the variable that is directly related to the level of earnings management is sales growth.